The impact of emotional intelligence on work engagement of registered nurses: the mediating role of organisational justice. Issue 15 (20th April 2015) - Zhu, Yun; Liu, Congcong; Guo, Bingmei; Zhao, Lin; Lou, Fenglan
<x xml:space="preserve">Abstract</x> Aims and objectives To explore the impact of emotional intelligence and organisational justice on work engagement in Chinese nurses and to examine the mediating role of organisational justice to provide implications for promoting clinical nurses' work engagement. Background The importance of work engagement on nurses' well‐being and quality of care has been well documented. Work engagement is significantly predicted by job resources. However, little research has concentrated simultaneously on the influence of both personal and organisational resources on nurses' work engagement. Design A descriptive, cross‐sectional design was employed. Methods A total of 511 nurses from four public hospitals were enrolled by multistage sampling. Data collection was undertaken using the Wong and Law Emotional Intelligence Scale, the Organizational Justice questionnaire and the Utrecht Work Engagement Scale‐9. We analysed the data using structural equation modelling. Results Emotional intelligence and organisational justice were significant predictors and they accounted for 44% of the variance in nurses' work engagement. Bootstrap estimation confirmed an indirect effect of emotional intelligence on work engagement via organisational justice. Conclusions Emotional intelligence and organisational justice positively predict work engagement and organisational justice partially mediates the relationship between emotional intelligence and work engagement. Relevance to clinical practice Our study supports the idea that enhancing organisational justice can increase the impact of emotional intelligence. Managers should take into account the importance of emotional intelligence and perceptions of organisational justice in human resources management and apply targeted interventions to foster work engagement.